Description Analysis of Warm Compress, NaCl 0,9%, and Aloe Vera Gel on Flebitis Degress in Children at Prof. Dr. Margono Soekarjo Purwokerto Hospital - Utami, Esti; Sholikhah, Umi; Anggraeni, Atika Dhiah; Wirasti, Unang (Proceedings Series on Health & Medical Sciences, 2025)
Phlebitis is a nosocomial infection caused by microorganisms and is characterized by clinical symptoms experienced by patients for 3x24 hours during the treatment period in the hospital. Appropriate handling both pharmacological and non-pharmacological in phlebitis can help minimize pain and injury in children. Compress is an alternative non-pharmacological treatment that can be done using several types of compresses, namely warm compresses, 0.9% NaCl compresses and aloe vera gel compresses. This type of research is quantitative research with descriptive analytic research design. The sample used amounted to 15 respondents children who are treated in the aster room of Prof. Dr. Margono Soekarjo Purwokerto Hospital with incidental sampling technique. The main variable in this study is the degree of phlebitis. This research data analysis is carried out interactively, in which there are three components, namely data reduction, data display, and conclusion drawing. The degree of phlebitis in children decreased every day after giving warm compresses, 0.9% NaCl compresses and aloe vera gel compresses and did not cause side effects during the intervention process with an average decrease on days 2 and 3. The results of giving warm compresses to 5 respondents showed a decrease in the degree of phlebitis with an average value of degree of phlebitis 3 to degree of phlebitis 2. While giving 0.9% NaCl compress 1 respondent recovered from phlebitis with a degree score of 0 from the previous degree score of 2. For the administration of aloe vera gel compresses on 5 respondents showed a decrease with an average value of degree of phlebitis 2 to 0 and 4 of the total 5 respondents given the intervention showed a degree score of 0 or recovered from phlebitis. Giving compresses helps reduce the degree of phlebitis in children so that it can be used as an alternative intervention against the incidence of phlebitis in children.